CO2 mitigation costs and ancillary benefits in the Nordic countries, the UK and Ireland: A survey - Snorre Kverndokk; Knut Einar Rosendahl (University of Oslo, Department of Economics, 2000)
This paper provides a survey of top-down modelling studies on mitigation costs and ancillary benefits in the Nordic countries, the UK and Ireland. Special emphasise is put on results concerning revenue recycling, double dividend, distributional effects, and ancillary benefits. According to the papers surveyed, modest emissions restrictions as those given by the Kyoto Protocol, can be met without substantial costs for the countries studied.
Keywords: D58; Q43; 330; Global warming; mitigation costs; double dividend; ancillary benefits; Kohlendioxid; Ökosteuer; Steuerinzidenz; Soziale Kosten; Großbritannien; Irland; Nordeuropa